2005
DOI: 10.4049/jimmunol.175.10.6893
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of TLR4/Type I IL-1 Receptor Signaling in the Induction of Inflammatory Mediators and Cell Death Induced by Ethanol in Cultured Astrocytes

Abstract: Activated astroglial cells are implicated in neuropathogenesis of many infectious and inflammatory diseases of the brain. A number of inflammatory mediators and cytokines have been proposed to play a key role in glial cell-related brain damage. Cytokine production seems to be initiated by signaling through TLR4/type I IL-1R (IL-1RI) in response to their ligands, LPS and IL-1β, playing vital roles in innate host defense against infections, inflammation, injury, and stress. We have shown that glial cells are sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
220
0
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(250 citation statements)
references
References 49 publications
11
220
0
9
Order By: Relevance
“…Furthermore, cell treatment with either high concentrations of ethanol or lipid raft disrupting agents (streptolysin O or saponin) inhibits ethanol-induced activation of the TLR4 signaling pathway (24). The effects of ethanol on TLR4 appear to be specific, because other short-chain n-alcohols do not induce TLR4 recruitment, although they slightly activate MAPKs signaling (23), and because other TLRs seems not to appear to be activated by ethanol (our unpublished results). We demonstrate, however, that ethanol activates TLR4/IL-1RI receptors in astrocytes (42).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cell treatment with either high concentrations of ethanol or lipid raft disrupting agents (streptolysin O or saponin) inhibits ethanol-induced activation of the TLR4 signaling pathway (24). The effects of ethanol on TLR4 appear to be specific, because other short-chain n-alcohols do not induce TLR4 recruitment, although they slightly activate MAPKs signaling (23), and because other TLRs seems not to appear to be activated by ethanol (our unpublished results). We demonstrate, however, that ethanol activates TLR4/IL-1RI receptors in astrocytes (42).…”
Section: Discussionmentioning
confidence: 99%
“…primary microglial and astrocyte cultures. 13 Similarly, morphine increases the expression of CCL2, CCL5 and IFNγ-inducible protein. 14 In vivo, systemic injections of either opioids and alcohol increases the expression of inflammatory mediators in key neuroanatomical areas associated with addiction such as the prefrontal cortex and hippocampus but not the cortex within mice.…”
Section: Evidence For Neuroimmune System Involvement In Addictionmentioning
confidence: 99%
“…The activation of TLR4 predominantly contributes to glial activation and the subsequent release of numerous proinflammatory cytokines (Mayfield et al, 2013). Importantly, these TLR4-related processes are involved in the behavioral and neuroinflammatory effects of drugs of abuse (Mayfield et al, 2013), as TLR4 activation has been shown to be integral to alcohol-induced glial activation and proinflammatory signaling (Alfonso-Loeches, Pascual-Lucas, Blanco, Sanchez-Vera, & Guerri, 2010;Blanco, Pascual, Valles, & Guerri, 2004;Blanco, Valles, Pascual, & Guerri, 2005;Fernandez-Lizarbe, Pascual, & Guerri, 2009), as well as alcohol's behavioral effects in rodents (Wu et al, 2012). Furthermore, in rodents, naltrexone attenuates proinflammatory TLR4-related signaling (Hutchinson et al, 2011) and blocks ethanolinduced glial activation and neuronal death (Qin & Crews, 2012), while (+) naloxone reduces acute alcohol-induced sedation and motor impairment (Wu et al, 2012).…”
Section: Naltrexone/naloxonementioning
confidence: 99%